Sequential coronary artery bypass grafting as the progress of coronary surgery. History of the issue - M.F. Rotari (Кардіохірургія та інтервенційна кардіологія)
The article presents the history of development and improvement of coronary surgery. The evolution of the method of sequential coronary bypass grafting is shown. Details of the types of anastomoses and features of surgical application techniques are presented. Features of hemodynamics of grafts with sequential coronary bypass are discussed.